The Potential of Stock Endowment in Indonesia as an Instrument for Islamic Economic Development - Catur Hayati Wulandari; Saparuddin Siregar; Aqwa Naser Daulay (MALIA: Jurnal Ekonomi Islam, 2023)
The potential of stock endowment in Indonesia for Islamic economic development holds great promise, especially given the majority Muslim population. This potential can be optimized to enhance the impact of stock endowment. This research aims to explore the utilization of stock endowment as a catalyst for Islamic economic growth, evaluate effective management strategies for stock endowment, and assess its potential in Indonesia. Using a qualitative approach, this study involves a literature review through metasynthesis. The findings indicate a significant potential for stock endowment in Indonesia, with investors continuously increasing. These funds could play a crucial role in addressing economic challenges within the principles of Islam, including education, healthcare, economic initiatives, and infrastructure development, if allocated optimally and comprehensively.